Mapping the literature of health education. - Schloman, B F (1997)
Health education is a relatively new multidisciplinary field concerned with educational programs that empower individuals and communities to play active roles in achieving, protecting, and sustaining their health. Its practitioners have bachelor's, master's, or doctoral degrees and work in educational, worksite, health facility, or agency settings. This bibliometric study was part of the Medical Library Association (MLA) Nursing and Allied Health Resources Section's Project for Mapping the Literature of Allied Health. It sought to identify the core journals in health education and to determine the extent to which these titles are covered by the standard indexing sources. Cited references appearing from 1991 through 1993 in articles of four journals published by the major professional associations in the field were analyzed. It was found that only thirteen journals supply one-third of all references in the study. Another eighty journals provide the second third. MEDLINE gives the best indexing coverage with nearly 69% of the journals receiving indexing for at least half of their articles, followed by EMBASE (52%) and PsycINFO (43%). Limited coverage is given by the Cumulative Index to Nursing and Allied Health Literature (16%) and ERIC (14%). The findings name titles that should be added by indexing services and those that should have more complete coverage.